2019
DOI: 10.1016/j.neuron.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Control of Reach Kinematics for Endpoint Precision

Abstract: Highlights d Cerebellar anterior interposed nucleus (IntA) neurons are modulated near reach endpoint d Closed-loop optogenetic manipulation of IntA adjusts reach kinematics in real time d IntA activity is variably engaged to enhance reach endpoint precision d Data provide a mechanistic insight into reach dysmetria

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
139
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 71 publications
12
139
0
Order By: Relevance
“…Previous studies, as well as the data presented here, highlight the decelerative phase of reaching movements as particularly important for adjusting to initial variability in reach kinematics, a process that is under direct neural control (Becker & Person, 2019;K. Novak et al, 2002).…”
Section: Intrinsic Kinematic Relationships Within Mouse Reaching Movesupporting
confidence: 56%
See 2 more Smart Citations
“…Previous studies, as well as the data presented here, highlight the decelerative phase of reaching movements as particularly important for adjusting to initial variability in reach kinematics, a process that is under direct neural control (Becker & Person, 2019;K. Novak et al, 2002).…”
Section: Intrinsic Kinematic Relationships Within Mouse Reaching Movesupporting
confidence: 56%
“…On the contrary, we argue that late-phase velocity asymmetries represent an adaptive response to the increased kinematic variability of distant (and hence faster) reaches. In our view, the inherent tradeoff between speed and accuracy could be mitigated by a shared neural mechanism of online kinematic control that adjusts for initial variability in service of endpoint precision (Becker & Person, 2019;J Messier & Kalaska, 1999). Without this neural mechanism intact, we predict a decrease in reach precision, potentially resembling the oscillatory dysmetria of cerebellar patients (Diener & Dichgans, 1992;Hore et al, 1991).…”
Section: Kinematic Evidence For the Importance Of Late-phase Controlmentioning
confidence: 84%
See 1 more Smart Citation
“…In line with findings of tightly coordinated activity in cortex and subcortical structures, recent work has highlighted the motor cortex as an input-driven dynamical system (Sauerbrei et al 2018) , where thalamic input is a prerequisite to drive movements as they happen. Cerebellar output appears essential not only for contributing to the precision of ongoing movements (Becker and Person 2019) , but also their planning in sensory discrimination tasks (Gao et al 2018;Chabrol, Blot, and Mrsic-Flogel 2019) . Thus, despite redundancy of motor systems as seen when lesioning selective regions -and assessment of motor performance after a recovery period-, both cortical and subcortical regions are required for successful motor planning and performance under natural conditions.…”
Section: Cerebello-cerebral Interactionsmentioning
confidence: 99%
“…3) and are likely important for localizing potential targets in space, while the SNr sends a robust inhibitory projection (Graybiel and Ragsdale, 1979), which likely conveys the necessary values associated with individual targets that are required to select among them (Handel and Glimcher, 2000;Basso and Wurtz, 2002;Sato and Hikosaka, 2002;Bryden et al, 2011). Additionally, cerebellar projections to the SCid may be critical in conveying predictive information regarding the position of effectors throughout the trajectory of the movement (Ohyama et al, 2003;Shadmehr, 2017;Owens et al, 2018;Becker and Person, 2019), ultimately mediating successful target acquisition. Indeed, studies performing muscimol inactivation of the cFN in monkeys making saccades to visual targets concluded that cerebellotectal projections might provide the SCid with information about the displacement needed to acquire spatial targets (Goffart et al, 1998).…”
Section: Discussionmentioning
confidence: 99%